Development of a Bi-Disciplinary Course in Forensic Science - Stacey L. Raimondi (American Society for Microbiology, 2013)
Forensic science programs and courses have traditionally been housed within chemistry departments at the college/university level, largely because the pioneers of the field were chemists who applied technology that was more chemical than biological in nature. However, with the development of such areas of study as DNA analysis, anatomical studies, and forensic entomology, it is becoming more and more important for forensic science students to have a strong biological background as well as a chemical background. Furthermore, while biology students are typically required to have extensive chemistry training as part of their major, the converse is not true for chemistry students. Therefore, it is possible that a student interested in forensic science could complete a major in chemistry and never have taken a biology class, leaving them woefully under-prepared for any type of masters program or career in forensic science immediately following graduation. Indeed, an examination of available positions in forensic science shows a large number of positions for DNA analysts for which the typical chemistry student would not be prepared without extensive biology training (http://www.aafs.org). Furthermore, positions for medical examiners or pathologists require extensive training in biology in addition to the continued medical training and residency programs. Therefore, it seems imperative that introductory forensic science courses adapt to these needs and be taught with a more bi-disciplinary approach in order to educate students on the whole field rather than one aspect. To that end, a new bi-disciplinary Forensic Science course was developed at Elmhurst College. This course was team-taught by a biology and a chemistry professor so that students would obtain a thorough understanding of the field and techniques used by both biologists and chemists. A description of this new version of a forensic science course follows, focusing on the addition of biology to a traditionally chemical course, the conclusions drawn upon completion of the course, and changes to be made in the future.